(untitled) (Research, Society and Development, 2021)
Telemedicine is an instrument that uses communication technology and makes it possible to provide access to health, solving problems in which distance would be a critical factor. Objective: To know the view of the professors of the medical course of a higher education institution in Palmas – Tocantins about telemedicine. Methodology: cross-sectional and descriptive research, with a quantitative and qualitative approach, developed with medical school professors from the 1st to the 8th period of Instituto Tocantinense Presidente Antônio Carlos – ITPAC Palmas. Data were collected from May to September, through an online questionnaire made available through GoogleForms® in order to analyze the view of the HEI professors on the growth and diffusion of telemedicine, containing 21 questions that addressed this theme. Results: 34.6% of the sample disbelieve in the full guarantee of safety/secrecy to the patient during remote care, and that consultations using telemedicine do not replace face-to-face follow-up, as many medical specialties lack the face-to-face doctor-patient relationship to achieve success in health care. It is noteworthy that the positive points were also identified, such as: greater reach to the population, possibility of contact between specialists and relief from the burden of the Unified Health System. Conclusion: The view of the professors regarding the use of telemedicine is multifaceted. It has negative points such as the difficulty of attending some specialties, and positive points such as: expanding access and sharing of knowledge among professionals. The expansion of studies and debates involving the subject is suggested.